2019
DOI: 10.1080/02827581.2019.1598484
|View full text |Cite
|
Sign up to set email alerts
|

Being one of the boys”: perspectives from female forest industry leaders on gender diversity and the future of Nordic forest-based bioeconomy

Abstract: Women working in the Nordic forest sector are underrepresented in top leadership positions, despite the female share increasing in higher education programs. Little research exists on this niche actor group in the forest sector context. To fill this gap, we assess perceptions of female leaders on the state of gender diversity in the Nordic forest industry, on the future of the forest sector in the bioeconomy, and on the potential contribution the Nordic forest industry can make to empower women, as promoted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
(40 reference statements)
1
11
1
Order By: Relevance
“…Women at Ada could therefore be seen as having a token position. However, unlike what would be expected from Kanter's (1977aKanter's ( , 1977b work and later studies of women in male-dominated contexts (see review by Watkins et al, 2018), including recent studies in Nordic countries (e.g., Alvinius et al, 2018;Baublyte et al, 2019;Nielsen and Madsen, 2019), we find that women's experiences of tokenism are more ambiguous and, remarkably, token women seem to even have a strong agentic role in defining Ada's corporate practices.…”
Section: Introductioncontrasting
confidence: 99%
“…Women at Ada could therefore be seen as having a token position. However, unlike what would be expected from Kanter's (1977aKanter's ( , 1977b work and later studies of women in male-dominated contexts (see review by Watkins et al, 2018), including recent studies in Nordic countries (e.g., Alvinius et al, 2018;Baublyte et al, 2019;Nielsen and Madsen, 2019), we find that women's experiences of tokenism are more ambiguous and, remarkably, token women seem to even have a strong agentic role in defining Ada's corporate practices.…”
Section: Introductioncontrasting
confidence: 99%
“…Another explanation may be the women's weaker agency in forestry in general. This is manifested by the by-stander position that women are offered and easily adopt in the management of the family forests (Vainio and Paloniemi 2013) as a result of forestry traditionally being a masculine practice (Baublyte et al 2019;Larasatie et al 2019). In families, the man more commonly takes care of forest management even if the woman formally owns the forest (Vainio and Paloniemi 2013), and hence the man is also more likely to use the Metsaan.fi eservice.…”
Section: Need For User-oriented Decision Support Services Is Evidentmentioning
confidence: 99%
“…The share of women working with forest owners is expected to be lower than their share of all personnel as the share of women from the members of the Forestry Expert Association (trade union for forest engineers) is 17% (Vennesland et al 2019). Homogeneity and formation of gendered practices participates in setting the social norms and practices in an organisation and thus they may hinder institutional change (Baublyte et al 2019). Herring (2009) found that homogeneity of the workforce may lead to less adaptability and innovation in his study about US for-profit businesses, whereas gender and racial diversity is associated with more customers, increased sales revenue, larger market share and larger relative profits.…”
Section: Role Of Organisations In Creating Changementioning
confidence: 99%
See 1 more Smart Citation
“…Ever since Kanter's theorizing about tokens, the need for women to take on masculine characteristics to compete successfully in male-dominated organizations has been described and discussed by researchers on gender and organizations (Miller 2004;Demaiter & Adams 2009;Powell et al 2009;Derks et al 2011;Kark et al 2012, Einarsdottir et al 2018Baublyte et al 2019). However, there is also research that nuances this image: societal gender dynamics as well as organizational dynamics change over the years, and expectations towards managers become more relaxed, allowing for greater variation including in gendered behaviors (Muhr 2011;Johansson et al 2019).…”
Section: Tokens Power and Possibilitiesmentioning
confidence: 99%